NaF-induced neurotoxicity via activation of the IL-1β/JNK signaling pathway. (15th March 2022) - Zhang, Chengzhi; Yang, Yanmei; Gao, Yanhui; Sun, Dianjun
Abstract: Excessive fluoride exposure can induce neuron apoptosis that is associated with neurodegenerative changes, but the mechanisms remain elusive. It has been suggested that chronic fluoride-induced microglia activation contributes to neuronal damage by producing pro-inflammatory cytokines. IL-1β, a pro-inflammatory cytokine released by activated microglia, is capable of inducing JNK phosphorylation and is associated with neurodegenerative diseases. In the current study, in vivo results demonstrate that excessive NaF impaired spatial learning and memory ability, microglia activation, and up-regulation of IL-1β in rats. Moreover, NaF exposure induced JNK pathway activation and associated apoptosis. These results were validated in vitro : NaF could induce BV-2 microglia cell activation and increase the concentration of IL-1β in the culture medium. When PC-12 cells were cultured with BV-2 CM or IL-1β for 24 h, the viability of PC-12 cells decreased, with enhanced apoptosis. In addition, IL-1 receptor antagonist (IL-1Ra) or SP600125 (JNK pathway inhibitor) diminished the IL-1β-induced activation of JNK pathway-mediated neuron apoptosis. Therefore, our study demonstrates that the IL-1β/JNK signaling pathway is involved in NaF-induced apoptosis of hippocampal neurons and cognitive dysfunction.